Pinocembrin Protects Against Dextran Sulfate Sodium-Induced Rats Colitis by Ameliorating Inflammation, Improving Barrier Function and Modulating Gut Microbiota - Hu, Lin; Wu, Chao; Zhang, Zijian; Liu, Mingchang; Maruthi Prasad, E.; Chen, Yu; Wang, Kai (Frontiers in Physiology, 2019)
Pinocembrin (PIN) is a natural flavonoid widely found in bee propolis with potent gastrointestinal protective effects. In consequence, PIN has great potential in preventing inflammatory bowel diseases while scant information is available. In this study, a dextran sulfate sodium (DSS)-induced rats ulcerative colitis model (3.5 % DSS in drinking water for 7 days) was applied to explore the protective effects of PIN on macroscopic colitis symptoms, inflammation, intestinal epithelial barrier function, and gut microbiota homeostasis. While DSS-treated rats showed severe colitis clinical symptoms and histological changes (colonic pathological damages and intestinal goblet cells loss), pre-administration of PIN (5 and 10 mg/kg, p.o.) for a week alleviated these symptoms. Pre-administration of PIN also suppressed the pro-inflammatory gene expressions and improved tight junction functions of colonic epithelial cells. Additionally, PIN administration reversed DSS-induced short chain fatty acid (SCFA) loss, and improved cecal digestion by increasing the gut microbial diversity assessed by 16S rRNA phylogenetic sequencing. Overall, our results suggest a wide spectrum of protective effects of PIN in preventing inflammatory bowel diseases.